Correlates of Attitudes Toward Dating Violence Among Police Cadets in China - Qu, Jia (International journal of offender therapy and comparative criminology, 2018)
Scholars have highlighted that incidents of dating violence are quite frequent among college students, and subsequent consequence can be devastating. A key factor that has been singled out in most studies on dating violence concerns an individual's attitudes toward dating violence. It is assumed that there is a link between one's attitudes and associated behaviors. The purpose of this study is to investigate correlates of attitudes toward dating violence among police cadets in a 4-year university in China. To the best of the authors' knowledge, this is the first time that police cadets were the subjects of research on this important topic. Besides several commonly adopted variables in the analysis in the United States, we incorporated three variables that were unique to this study (the assistance-oriented police strategy, internship experience, and knowing anti-domestic violence law). The findings revealed that preference of gender-role, perceptions of the nature of dating, and police strategies have significant effect on cadets' sentiment of dating violence. We also discussed the limitations of this study and highlight several areas that future research needs to focus on.